Racial/Ethnic Test Score Gaps and the Urban Continuum - Douglas J. Gagnon; Marybeth J. Mattingly (Journal of Research in Rural Education, 2018)
Research is just beginning to describe with precision determinants of racial and ethnic achievement gaps. Work by Reardon, Kalogrides, and Shores found that factors such as parental income, parental education, and segregation are the strongest predictors of achievement gaps. In this study we expand this line of inquiry to examine the role of urbanicity. Given the considerable historical, cultural, economic, and educational diff erences between city and rural locales, there is reason to suspect that the forces which shape their achievement gaps are diff erent as well. We examine White-Black and White-Hispanic test gaps across thousands of Local Education Agencies (LEAs), fi nding that rural LEAs have White-Black and WhiteHispanic achievement gaps 16% and 22% smaller, respectively, than those found in city schools. Moreover, socioeconomic factors have a diff erent relationship to gaps in more rural as opposed to more urban places.